Analisis Sensitivitas Parameter Kalibrasi Dalam HEC-HMS - Meiki Prayudi; Yohanna Lilis Handayani; Bambang Sujatmoko (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2017)
Lubuh River which is located in the stems of Rokan Hulu Riau Province is one of the rivers that often have overflow water on rainy season that happen flood. Resolve problems that happened, there is a hydrological modeling to predict debitwith software tools Hydrologic Engineering Center-Hydrologic Modeling System. This research took the case study of Automatic Water Level Recorder station of Pasir Pengaraian in Rokan watershed with the length of the data for six days(May 1, 2012 00:00 to May 6, 2012 23:00). Based on the results calibration using six parameter, then be obtained parameter have sensitivity is greater than the parameter other that is parameter Initial and Constant-Constant Rate because ofchange parameter values 99,64% produce changes volume into 92,8%.Keyword: hydrological modeling, predict debit, calibration, HEC-HMS, sensitivity parameter